Efektivitas Pemanfaatan Air Lindi Sisa Pakan Maggot Sebagai Poc Terhadap Pertumbuhan Selada Air - Yehuda Devid Welem Sefaniwi; Alfred B Alfons; Bambang Suhartawan (Journal of Innovative and Creativity, 2025)
Organic waste management in urban areas poses significant environmental challenges. Black Soldier Fly (BSF) maggot cultivation offers a sustainable solution by converting organic waste into valuable resources. However, the leachate produced during this process remains underutilized despite its potential as liquid organic fertilizer (LOF). This study aimed to evaluate the effectiveness of maggot feed residue leachate as liquid organic fertilizer on watercress (Nasturtium officinale) growth in hydroponic systems and determine the optimal concentration for maximum plant performance. An experimental study using Completely Randomized Design (CRD) was conducted with five LOF concentration treatments (0%, 5%, 10%, 15%, and 20%) and three replications, totaling 15 experimental units. The research was carried out at BTN Skyland, Abepura, Jayapura City, Papua, from February to September 2025. Parameters measured included plant height, leaf number, and fresh weight. Data were analyzed using one-way ANOVA followed by Tukey HSD post-hoc test. ANOVA analysis revealed highly significant effects (p < 0.001) of LOF concentration on all growth parameters. The optimal concentration was found at 10% LOF, showing remarkable improvements: 50% increase in fresh weight (30g vs 20g), 60-67% increase in leaf number (18-20 leaves vs 10-12 leaves), and 57-67% increase in plant height (20-22 cm vs 12-14 cm) compared to control. A dose-response pattern following an inverted parabolic curve was observed, with stimulation zone at 5-15% concentrations and inhibition zone at 20% concentration. Maggot feed residue leachate proved highly effective as liquid organic fertilizer for hydroponic watercress cultivation. The 10% concentration represents the optimal application rate, supporting sustainable urban agriculture while addressing organic waste management challenges. This technology demonstrates successful implementation of circular economy principles in urban farming systems.